Teacher politeness: A cross-cultural comparison in ESL classrooms - Soheim, Yasmine Mostafa (AUC Knowledge Fountain, 2015)
There have been a plethora of studies investigating politeness in different segments of the society. Research on classroom politeness has addressed many different themes, given its tactical role in the teacher-student relationship. For instance, a teacher could intentionally or unintentionally define her/his social distance with the students by means of politeness strategies employed in the classroom. In Egypt, with the growing number of private educational institutions, where the English language is overtly foregrounded, many native speakers are hired as ESL teachers. On one hand, these teachers, who just arrived from their home countries where the teaching and learning attitudes might be different, engage in their work with a set of expectations of their Egyptian students. On the other hand, those students also have expectations of their ESL teacher; for example, they may expect more assistance and availability from their teachers' side. These differences in expectations could be problematic, as meeting each other's expectations could be hindered because of cross-cultural barriers. Based on Brown and Levinson's politeness theory, the present study compares teacher politeness strategies in ESL classroom from a cross-cultural perspective. First, it examines politeness strategies used by American and Egyptian instructors in an English-medium university context in Egypt by investigating how Egyptian and American teachers use positive and negative politeness in their ESL classrooms and with what frequency. The second focus is mainly concerned with the explanation of the American and Egyptian teachers' preferences of politeness strategies. Because of the exploratory and qualitative nature of the study, the researcher observed and discerned the indicators of positive and negative teacher politeness strategies during 10 classroom observations and four interviews. Five Americans and five Egyptians teaching in the undergraduate Rhetoric and Composition department at an American university in Egypt represented the main participants of the study. Qualitative analysis of the findings revealed that American participants used slightly fewer positive politeness strategies in the classroom than their Egyptian colleagues. In contrast, the American teachers participating in the study employed more negative politeness strategies compared to the Egyptian instructors. Their dissimilar preferences of politeness strategies could be justified by their different expectations from their students. Regardless of their cultural background, in the classroom, teachers satisfied their students' positive face by employing positive politeness strategies such as offering help and compliments. Further, the students’ negative face could be saved by making use of negative politeness strategies, such as hedging when giving feedback, for example. The findings of the study implied the potential usefulness of offering insightful seminars and workshops highlighting the cultural differences and similarities to new teachers, who might have a different cultural background from their students'.